متطلبات التخطيط الاستراتيجي في جامعة انجمينا بجمهورية تشاد من وجهة نظر أعضاء هيئة التدريس - أحمد، زكريا محمد; أحمد، حسن عبدالمالك محمود; علي، شاذلي يونس (جامعة الأزهر - كلية التربية, 2021)
هدفت الدراسة بشكل رئيسي إلى تقديم مجموعة من المقترحات لتطوير التخطيط الاستراتيجي في جامعة انجمينا بجمهورية تشاد وذلك من خلال التعرف على مدى توافر متطلبات التخطيط الاستراتيجي في جامعة انجمينا بجمهورية تشاد، والتعرف على معوقات التخطيط الاستراتيجي في جامعة انجمينا، واستخدمت الدراسة المنهج الوصفي، وتم تطبيق الاستبانة على عينة عشوائية من أعضاء هيئة التدريس، بلـغ عـددهم (102) عـضـوا، وتوصلت الدراسة إلى أن درجـة تـوافـر إجمالي مؤشرات التخطيط الاستراتيجي تقع في مستوى متوسطة من وجهة نظر أعضاء هيئة التـدريس بمتوسـط حـسابي (1.78)، وأن بعـض متطلبـات التخطيط الاستراتيجي في جامعـة انجمينـا تـتـوافـر في مستوى متوسطة وتحتاج إلى تعزيز؛ كوضـوح الرؤية والرسالة وواقعيـة الأهـداف، كما كشفت الدراسـة عـن مجموعة من المعوقات التي تحـد مـن تحقيق التخطيط الاستراتيجي في جامعة انجمينا كعدم وجـود فـريـق مدرب للقيام بالتخطيط الاستراتيجي، وقلة البيانات والمعلومات اللازمة للقيام بعملية التخطيط الاستراتيجي، وأوصت الدراسـة بـضـرورة تكوين فريق مختص بعمليات الجـودة والتخطيط الاستراتيجي في الجامعة، ومشاركة أعـضاء هيئة التدريس في عملية التخطيط الاستراتيجي، والقيام بالدورات التدريبية العملية الفعالة للعمداء ورؤساء الأقسام والعاملين والمنتسبين للجامعة في مستجدات الفكر الإداري ونظرياته، وتخصيص الموارد الماليـة الكفيلـة بتـوفير متطلبات التخطيط الاستراتيجي، والاستفادة مـن نتائجه، كمـا قـدمت الدراسة مجموعة من المقترحات التي تساهم في تطوير واقع التخطيط الاستراتيجي في جامعة انجمينا.
The study mainly aimed to present a set of proposals to develop strategic planning at the University of Ndjamena in the Republic of Chad by identifying the availability of strategic planning requirements and obstacles at the University of Ndjamena in the republic of Chad. The study made use of the descriptive approach, and a questionnaire was administered to a random sample of faculty members (totaling 102). The study results revealed that the degree of availability of the total strategic planning indicators is at a medium of the total level from the viewpoints of teaching staff with an arithmetic mean of (1,78). Some of the strategic planning requirements at Ndjamena University are at medium level and need to be strengthened, such as clarity vision, mission and realism of goals. The study also revealed a set of obstacles such as the lack of a trained team to undertake strategic planning, and the lack of data and information that are used for strategic planning process, and the weakness of the strategic plan. The study recommended the necessity of forming a team specialized in quality and strategic planning, and participation teaching staff for strategic planning process, and conducting effective practical training courses for deans, and departments' heads. The study also recommended allocating financial resources to provide the requirements at the University, the study also presented a set of proposals to developing the strategic planning at the University of Ndjamena in the Republic of Chad. Strategic planning at the University of Ndjamena in the Republic of Chad.
Keywords: التخطيط الاستراتيجي -- أعضاء هيئة التدريس -- الجودة الشاملة -- الموارد المالية -- تشاد